LEGAL CONSEQUENCES OF DISPOSAL MASK WASTE ON ENVIRONMENT: Based on Law No. 32/2009 Concerning Environmental Protection and Management - Evandra, Andreas Raditya David; Priyati, Sri (jfpublisher, 2022)
The use of masks in an effort to prevent Covid-19 is indeed quite effective. Unfortunately, the potential problem from the use of disposable masks is the waste will have an impact on environmental pollution because the mask material is made of polypropylene which is a type of plastic that is difficult to decompose.Therefore, the objective of this research is to find out the importance of preserving the environment by paying attention to waste around the environment and to analyze important to dispose of waste through proper processes and management for preventing the negative impact on environment that will cause environmental damage and pollution. The method used is descriptive qualitative combined with normative legal research and statutory, conceptual, historical, and comparative approaches. The legal materials used in this research are primary legal materials, such as Law No. 32/2009 concerning the environment protection and management, Law No. 18/2008 concerning waste management, Government Regulation No. 101/2014 concerning the management of hazardous waste and toxic materials (B3) as secondary legal materials.